AGD: Aneurysm Gene Database. (26th September 2018) - Sun, Ruya; Cui, Chunmei; Zhou, Yuan; Cui, Qinghua
Abstract: An aneurysm is an outward bulge on an arterial wall. Aneurysms are becoming a serious public health concern as the worldwide population ages. Unfortunately, no effective drugs have been developed for aneurysms to date. In addition, aneurysms may be associated with grave prognosis due to conditions such as ruptures and recurrence. Altogether, these factors make earlier aneurysm prevention, diagnosis and intervention strategies even more important. A bioinformatics resource for aneurysm-associated molecules would be helpful for addressing the above issues; however, such a tool is not yet available. In this study, we developed Aneurysm Gene Database (AGD) for the above purpose. AGD contains 1472 aneurysm-gene associations, including 29 types of aneurysms, 967 protein-coding genes, 29 miRNAs, 6 lncRNAs and several other types of molecules. Users can search, browse and download content in AGD. We believe that AGD is a valuable resource that can help us better understand aneurysms and discover novel treatment targets.